The Potential Distribution of Pythium insidiosum in the Chincoteague National Wildlife Refuge, Virginia - Jara, Manuel; Holcomb, Kevin; Wang, Xuechun; Goss, Erica M.; Machado, Gustavo (Frontiers in Veterinary Science, 2021)
Pythium insidiosum is a widespread pathogen that causes pythiosis in mammals. Recent increase in cases reported in North America indicates a need to better understand the distribution and persistence of the pathogen in the environment. In this study, we reconstructed the distribution of P. insidiosum in the Chincoteague National Wildlife Refuge, located on Assateague Island, Virginia, and based on 136 environmental water samples, collected between June and September of 2019. The Refuge hosts two grazing areas for horses, also known as the Chincoteague Ponies. In the past 3 years, 12 horses have succumbed to infection by P. insidiosum. Using an ecological niche model framework, we estimated and mapped suitable areas for P. insidiosum throughout the Refuge. We found P. insidiosum throughout much of the study area. Our results showed significant monthly variation in the predicted suitability, where the most influential environmental predictors were land-surface water and temperature. We found that June, July, and August were the months with the highest suitability for P. insidiosum across the Refuge, while December through March were less favorable months. Likewise, significant differences in suitability were observed between the two grazing areas. The suitability map provided here could also be used to make management decisions, such as monitoring horses for lesions during high risk months.